LEGAL ANALYSIS AND REGULATION OF MAJALLAT AL-AHKAM AL-ADLIYYAH IN ISLAMIC FINANCE - Zanirah Mustafa@Busu; Noraini Junoh; Mohd Miqdad Aswad Ahmad (Journal of Islamic, Social, Economics and Development, 2024)
The Majallat al-Ahkam al-Adliyyah or the Book of Justice covers the first Islamic civil law introduced in Islam, during the Ottoman Empire in the 19 th century. Majallat al-Ahkam al-Adliyyah covers many types and problems of fiqh al-muamalat (Islamic commercial legislation) which mostly depends on the opinions of the Hanafi Maddhab. This research also describes Majallat al-Ahkam al-Adliyyah from the aspect of the research on the understanding of Fiqh and the law as discussed in this article. This research aims to explain the rules of fiqh found in Majallat al-Ahkam al-Adliyyah as a form of reform that can be developed and implemented today. Researcher focused on the development of the method of fiqh through the works of bibliography before the formulation of the magazine, the record of the writing of the magazine itself and the aspects contained in it. The research method using qualitative design through analysis of text content on the book Majallat al-Ahkam al-Adliyyah. Data and information are obtained from documents, journals and references related to the scope of the research. The results of this study found that the jurisprudence of muamalat law from an Islamic perspective is very relevant in the context of the Islamic banking system today. In general, the collection of fiqh methods requires continuous effort because it is not limited to the aspects of reform brought in the formulation of Majallat al-Ahkam al-Adliyyah alone or even in line with the development of the times. Finally, it is our hope that this small contribution of writing will be able to help increase the knowledge of the Muslim community on Islamic law, especially in the chapter on the Islamic financial and banking system.